2000
DOI: 10.1148/radiographics.20.1.g00ja0629
|View full text |Cite
|
Sign up to set email alerts
|

CT and MR Imaging Findings of Bowel Ischemia from Various Primary Causes

Abstract: Ischemic bowel disease represents a broad spectrum of diseases with various clinical and radiologic manifestations, which range from localized transient ischemia to catastrophic necrosis of the gastrointestinal tract. The primary causes of insufficient blood flow to the intestine are diverse and include thromboembolism, nonocclusive causes, bowel obstruction, neoplasms, vasculitis, abdominal inflammatory conditions, trauma, chemotherapy, radiation, and corrosive injury. Computed tomography (CT) or magnetic res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
112
1
4

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 257 publications
(119 citation statements)
references
References 33 publications
2
112
1
4
Order By: Relevance
“…Most common locations include splenic flexure and rectosigmoid colon. Segmental wall thickening with layered appearance or target sign is seen on enhanced scan [15]. Pneumatosis may be seen in advanced disease.…”
Section: Enhancement Patternmentioning
confidence: 99%
“…Most common locations include splenic flexure and rectosigmoid colon. Segmental wall thickening with layered appearance or target sign is seen on enhanced scan [15]. Pneumatosis may be seen in advanced disease.…”
Section: Enhancement Patternmentioning
confidence: 99%
“…In addition, the presence of barium may compromise subsequent diagnostic tests, such as computed tomography (CT) and angiography [32] . Magnetic resonance imaging has shown promising results in detecting mesenteric ischemia but remains a slow-processing technique that seems to be inadequate in an emergent situation such as AMI [39,40] . Mesenteric duplex sonography is a highly userdependent modality that can only confirm diminished blood flow in the trunks of the mesenteric blood vessels.…”
Section: Imaging Studiesmentioning
confidence: 99%
“…Changes that have been reported include bowel wall thickening and edema, submucosal hemorrhage, increased or decreased enhancement of the bowel wall, mesenteric stranding or fluid, and pneumatosis intestinalis. [10][11][12][13] However, these morphologic descriptions are not adequate for the early detection of reversible bowel ischemia. A recent study reported that spiral CT demonstrated a sensitivity and specificity of 64% and 92%, respectively, for diagnosing mesenteric ischemia.…”
mentioning
confidence: 99%